Gold(III) Complexes with 2-(1-Ethylbenzyl)pyridine as Promising Antimicrobial and Antitumor Agents - Antonio Zucca; Bruna Canu; Maria I. Pilo; Sergio Stoccoro; Giacomo Senzacqua; Sara Fais; Giuseppina Pichiri; Alessandra Scano (Molecules)
Antimicrobial resistance (AMR) is one of the most urgent public health problems worldwide; multidrug resistance (MDR) is also of concern. In an effort to find new classes of antibiotics, recent studies have found that coordination compounds of noble metals show promising biological effects both in vitro and in vivo, deserving attention as a new class of possible antimicrobial agents. Metal ions in biological systems can essentially have two roles: structural or functional. In the former, the metal ion serves to stabilize structures, especially proteins, while in the latter, the metal is involved in bio-site reactivity (essentially in metallo-enzymes). Two new complexes with 2-(1-ethyl-benzyl)pyridine (pyeb), one monodentate adduct and one cyclometalated ([Au(pyeb)Cl3] and [Au(pyeb-H)Cl2], respectively), have been synthesized, characterized, and tested against Gram-positive and Gram-negative bacteria, as well as yeasts, revealing promising antibacterial and antibiofilm properties. The two complexes have been thoroughly characterized by means of 1D and 2D NMR spectroscopy, as well as by cyclic voltammetry, conductivity measurements, FT-IR, and elemental analysis. The study showed that the two derivatives are structurally and chemically different, with the cyclometalated complex being chemically and electrochemically more stable. Antimicrobial assays demonstrated that solutions of the monodentate adduct and of the cyclometalated complex have inhibitory and antibiofilm effects against the pathogenic bacteria E. coli, K. pneumoniae, S. aureus, and S. pyogenes but were unable to reveal a fungicidal effect on C. albicans. A preliminary study was conducted to assess the anti-cancer activity of the compounds, and treatments with the gold compounds also resulted in a significant reduction in the metabolic activity of HT29 colon cancer cells.